PTH-337 Personalising radiotherapy in locally advanced rectal cancer: can macrophages within the microenvironment predict response to radiotherapy?. (22nd June 2015) - Shaikh, S; Noshirwani, A; West, NP; Perry, SL; Maisey, T; Jayne, DG
Abstract : Introduction: While neoadjuvant radiotherapy is the standard of care in locally invasive rectal carcinoma (LIRC), only half of patients show a response. A predictive test enabling better patient selection could avoid unneccessary radiation exposure to poor responders. Macrophages within the tumour immune microenvironment with tumoricidal M1 and tumour-protective M2 phenotypes could be modulating this response. This study investigated the possible predictive value of M1 and M2 subpopulations in identifying patients' likely response to short-course preoperative radiotherapy. Method: Biopsy samples were taken from 29 patients with locally invasive rectal carcinoma before treatment with short course radiotherapy and surgical specimens obtained after resection following short-course preoperative radiotherapy. Dual-staining immunohistochemistry was performed with CD68 as macrophage marker, HLA-DR as M1 marker, and CD163 as M2 marker. Samples were scored for hot-and-random spots by Nuance software (version 3.0.2) and compared with patients' outcome data. Tumour response was measured by assessment of reduction of tumour-cell density. Results: Samples revealing a low score for HLA-DR positive M1 macrophages exhibited a better response to short-course radiotherapy with up to 80% (median 80·38% [IQR 46·94–84·73]) reduction in the tumour cell density. On the other hand those with a high score exhibited a poor response with only up to 20% (20·26 [0–48·19]) reduction. The difference in response between the two groups was significant (p = 0·017). No such trends were observed for CD163 + M2 macrophages. The ratio of HLA–DR+ to CD163 + macrophages for biopsy and resection samples was significantly different showing a drop in the HLA-DR positive macrophages in the resection samples (p 0.024). The mean of the difference between the biopsy (median 2·53 [IQR 1.98 – 3.08]) and resection (1·38 [IQR 0.96 – 1.8]) was 1·15 (p = 0·024). Conclusion: Patients with a variable macrophage phenotype composition within biopsy samples from patients with locally invasive rectal carcinoma respond differently to short-course preoperative radiotherapy. Further investigation involving a panel of macrophage and other immune-cell markers could verify and validate these findings and develop them as predictive tests identifying good responders to radiotherapy in patients with locally invasive rectal carcinoma. Disclosure of interest: None Declared.